Analysis of Patient Satisfaction Level Towards Services - Christina Ary Yuniarti; Wachid Dachirin; Namira Isthi Afiya; Adinda Mutiara Cahaya Insani (Indonesian Journal of Global Health Research, 2025)
Patient satisfaction is an essential indicator of healthcare quality, directly linked to trust and patient loyalty. This study aims to analyze patient satisfaction levels toward the services provided at Kembang Arum Clinic, Kalipancur, Ngaliyan District, Semarang City. A quantitative approach was employed using a survey design, with data collected through questionnaires covering five dimensions of satisfaction: tangibles, reliability, responsiveness, assurance, and empathy. Data were gathered from a sample of patients within a specified period and analyzed descriptively. The findings indicate the highest satisfaction levels in the empathy dimension (74.6%) and reliability (66%), while the assurance dimension had the lowest satisfaction level (58.33%). Certain aspects, including waiting times and physical facilities, require improvement to enhance service quality. The conclusion highlights the need for improved medical facilities and better time management to ensure higher patient satisfaction levels.